2024
DOI: 10.1002/admt.202301658
|View full text |Cite
|
Sign up to set email alerts
|

Full‐Range On‐Body Strain Sensor of Laser‐Induced Graphene Embedded in Thermoplastic Elastomer via Hot Pressing Transfer for Monitoring of the Physiological Signals

Jiaqi Liu,
Dun Wu,
Chunlin Liu
et al.

Abstract: Acquiring physical and mechanical strain information of the human body with wearable strain sensors can provide essential data from personal healthcare to human‐machine interfaces and others. Recent research reveals that CO2 laser scribing can convert polyimide films into porous graphene sponges under ambient atmospheres. However, the electrically conductive laser‐induced graphene (LIG) film mismatches with the tough and rigid plastic substrates when it is employed as stretchable strain sensors. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Although the composite materials provide the superior mechanical stability required for strain sensing, the elastomer covering part of the LSG surface inevitably impairs its performance as a sensing electrode. Recently, Liu et al observed plenty of carbon vacancies in the crystalline lattice of LSG by examining the microstructure of atom-layer thin LSG flakes [ 42 ]. These atom-level configured defects may induce fractures or delamination within LSG sponges.…”
Section: Leg-based Biophysical Sensingmentioning
confidence: 99%
“…Although the composite materials provide the superior mechanical stability required for strain sensing, the elastomer covering part of the LSG surface inevitably impairs its performance as a sensing electrode. Recently, Liu et al observed plenty of carbon vacancies in the crystalline lattice of LSG by examining the microstructure of atom-layer thin LSG flakes [ 42 ]. These atom-level configured defects may induce fractures or delamination within LSG sponges.…”
Section: Leg-based Biophysical Sensingmentioning
confidence: 99%